Influence of the processing parameters on the electrocaloric effect of poly(vinylidene fluoride–trifluoroethylene) copolymers. Issue 5 (5th October 2016) - Yao, Yongtao; Hou, Guanghua; Li, Nannan; Zhou, Tianyang; Liu, Liwu; Liu, Yanju; Leng, Jinsong
ABSTRACT: The influence of the processing parameters on the electrocaloric effect of a ferroelectric polymer was investigated. A normal ferroelectric poly(vinylidene fluoride–trifluoroethylene) [P(VDF–TrFE)] (55:45 mol %) copolymer was selected and fabricated. The crystallinity, microstructure, mechanical properties, and refrigeration capability of this copolymer were characterized with X‐ray diffraction, scanning electron microscopy, differential scanning calorimetry, and thermogravimetric analysis, respectively. We found that N, N ‐dimethylformamide was the most suitable solvent for enhancing the crystallinity of the copolymer film. In combination with the consideration of the effect of the processing parameters on the microstructure of copolymer, a lower spin‐coating temperature and annealing temperature at 140 °C gave the highest crystallinity and uniform microstructure without defects. The highest temperature change was 12.13 °C when the copolymer film was operated at 110 °C under a higher electric field. The direct measurement of the refrigeration was carried out with an IR thermometer. We found that the P(VDF–TrFE) copolymer film had a considerable refrigeration capability, which increased as the applied electric field strength increased before electric breakdown. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44413. Abstract :